Urban measurements of atmospheric nitrous acid: A caveat on the interpretation of the HONO photostationary state. Issue 21 (13th November 2013) - Lee, B. H.; Wood, E. C.; Herndon, S. C.; Lefer, B. L.; Luke, W. T.; Brune, W. H.; Nelson, D. D.; Zahniser, M. S.; Munger, J. W.
Abstract [1] Numerous studies infer the existence of an "unknown" daytime HONO source based on the assumption that HONO is at photostationary state (PSS). Secondary HONO production rate as high as 1.1 ppb hr−1 can be estimated from this approach, based on measurements made during the Study of Houston Atmospheric Radical Precursors campaign in May of 2009. We argue, however, that the PSS assumption might not have been valid because the transport time from nearby NOx emission sources to the measurement site was likely less than the time required for HONO in vehicle exhaust to reach PSS. Using a chemical box model, we demonstrate that there is initially net HONO formation as high levels of NO in exhaust react with ambient OH. Net production is followed by a period of net HONO loss dominated by photolysis that is sustained for several minutes to hours depending on time of day. The presence of relatively fresh exhaust in sampled air can partially, if not fully, account for the observed measurement PSS discrepancy. We also show that a large fraction of the observed nighttime increase in HONO/NOx ratio is explained by NO2 oxidation. These results do not rule out the existence of an unexplained secondary HONO source but suggest that great care must be exercised when applying the PSS method to quantify its strength.